Internal validation of STRmix™ – A multi laboratory response to PCAST. (May 2018) - Bright, Jo-Anne; Richards, Rebecca; Kruijver, Maarten; Kelly, Hannah; McGovern, Catherine; Magee, Alan; McWhorter, Andrew; Ciecko, Anne; Peck, Brian; Baumgartner, Chase; Buettner, Christina; McWilliams, Scott; et al.
Highlights: The analysis of 2825 mixtures from 31 laboratories with the probabilistic genotyping software STRmix™ is reported. Less discriminatory LR s occur both for donors and non-donors at low template (for the donor in question) and at high contributor number. We were unable to isolate an effect of allelic overlap. Any apparent effect appears to be largely confounded with increased contributor number. Abstract: We report a large compilation of the internal validations of the probabilistic genotyping software STRmix™. Thirty one laboratories contributed data resulting in 2825 mixtures comprising three to six donors and a wide range of multiplex, equipment, mixture proportions and templates. Previously reported trends in the LR were confirmed including less discriminatory LRs occurring both for donors and non-donors at low template (for the donor in question) and at high contributor number. We were unable to isolate an effect of allelic sharing. Any apparent effect appears to be largely confounded with increased contributor number.